Assessment and Monitoring of Land Management Plans in the Municipalities of Colombia - Camelo Garzón, Ángela Natalia; Solarte-Pazos, Leonardo; López, Oswaldo (Sociedad y Economía, 2015)
The Planning Process for land use that is being performed in Colombia according to Law 388, issued in 1997 (Land Development Law), is perhaps one of the most substantial chan- ges it has undergone the exercise of planning by municipalities in Colombia. However, there is still a long way to go in order to implement a true culture of comprehensive plan- ning and land management. In this context, the present article aims to show the results of a research project which proposes an alternative approach to monitoring and evalua- ting management of land use planning for municipalities in Colombia, in the specific context of city planning. This new approach integrates traditional urban management elements with public and social management assessment focus.